Characterisation, modelling and design of cut-off wavelength of InGaAs/GaAsSb type-II superlattice photodiodes. (1st February 2023) - Petticrew, Jonathan; Ji, Yuting; Han, Im Sik; White, Benjamin; Evirgen, Axel; Reverchon, Jean-Luc; Hopkinson, Mark; Tan, Chee Hing; Ng, Jo Shien
Abstract: InGaAs/GaAsSb type-II superlattice (T2SL) photodiodes grown on InP substrates are an alternative detector technology for applications operating in the short wavelength infrared band. Their cut-off wavelengths are heavily influenced by the thickness and material composition of InGaAs and GaAsSb used in the T2SL. We present a single band k.p. model performed using a finite difference approach in nextnano validated against two T2SL photodiode wafers and results from literature. These photodiode wafers cover both lattice matched and strained GaAs1− x Sb x compositions ( x = 0.40, wafer A and 0.49, wafer B). The validation data covers temperature dependence of cut-off wavelengths (obtained from phase-sensitive photo response data) from 200 K to room temperature. The cut-off wavelengths were found to reduce at 1.32 nm K −1 for wafer A and 1.07 nm K −1 for wafer B. Good agreement was achieved between the validation data and nextnano simulations, after altering the GaAs1− x Sb x valance band offset (VBO) bowing parameter to −1.06 eV. Using this validated model, we show that the wavefunction overlap drops significantly if the GaAsSb barrier is thicker than the InGaAs well layer, hence defining the upper limit of the barrier layer. This validated model is then used to demonstrate that there is a linear dependence between the maximum achievable wavefunction overlap and cut-off wavelength of a lattice matched InGaAs/GaAsSb T2SL. We also found that the adoption of a 5 nm/3 nm InGaAs/GaAsSb T2SL structure offers an improved wavefunction overlap over the more common 5 nm/5 nm InGaAs/GaAsSb T2SL designs. The data reported in this paper is available from doi: 10.15131/shef.data.20310591.